ANALISIS PERCEIVED USABILITY SEBAGAI FAKTOR YANG MEMOTIVASI PENGGUNA UNTUK TERUS MENGGUNAKAN MOBILE PAYMENT: POST ADOPTION MODEL DAN SEM-PLS - Lante, Gabriella; Wurarah, Rully N; Inan, Dedy I (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2024)
Mobile Payment (m-payment) is a non-cash payment system acclaimed for its ease, practicality, and smartphone accessibility from any location and at any time. M-payment encompasses various transaction functions beyond mere payment, extending to diverse transactional activities. This research aims to elucidate the influence of perceived usability factors, namely perceived usefulness, perceived ease of use, and perceived enjoyment, on user motivation to persistently utilize m-payment in West Papua Province. The theoretical framework of the Expectation-Confirmation Model serves as the lens for this investigative process. Two control variables, age, and gender, are employed to scrutinize the detailed impact of these factors across distinct user groups using Partial Least Square-Structural Equation Modeling (SEM-PLS). Out of 250 valid m-payment user respondents obtained through an online questionnaire via Google Forms, the results reveal that perceived usability significantly impacts motivating users to continue employing m-payment as a non-cash payment method. The research model yields R2 values of 0.735 and 0.560 for satisfaction and continuance usage, respectively, indicating substantial and moderate predictive strength. Furthermore, this research informs that control variables, age, and gender, offer nuanced insights into the influence of perceived usability factors within these specific user groups. Detailed discussions and conclusions are elaborated in this research.